Fracture toughness of kenaf mat reinforced polyester composite - Radif, Zainab Shakir; Ali, Aidy (Universiti Putra Malaysia Press, 2011)
The fracture behaviour represents the most critical issue in the automotive and aerospace engine fields. Thus, the objective of this study was to estimate and analyze the crack criteria by using the Mathematical laws that were limited in E 1820 standard and the results affirmed by applying the numerical solutions of ANSYS to estimate the fracture toughness value KIC, besides the energy release rate of biomass composite. The specimens were prepared from different percentage of kenaf mat (KM) and unsaturated polyester resin (UP) 20% KM â€“ 80% UP and 40% KM â€“ 60% UP, respectively, as well the other composite properties which were calculated using the stress-strain data. The fracture characterizations of this composite were carried out using the compact tension (CT) specimen that was commonly used to determine Mode-I fracture properties. The fracture toughness has been found to be independent of pre-crack length. Meanwhile, the tests were performed at room temperature. The numerical simulations of the ANSYS model results demonstrated a good agreement between the experiments computed results of the fracture toughness. The fracture toughness KIC of 20% KM â€“ 80% UP and 40% KM â€“ 60% UP was equivalent to 0.76 MPa√m and 2.0 MPa√m, respectively. Thus, the fracture propagation is dependent on the fibre percentage of the composite. On the other hand, there are unlimited mechanisms of crack paths derived from randomly kenaf mat packs, particularly in the frontal process zone of crack tip.